К вопросу о формировании глобальной правовой системы - Оборотов, Юрий Николаевич; Оборотов, Юрій Миколайович; Oborotov, Jurij (My University, 2011)
In the process of globalization the national, integrative and international law are changing, what involves the forming of the new legal reality — global law. Global law has a specific content, which expressed in the phenomenon of «soft law», and implicates new special subject with peculiar legal status.
Оборотов Ю. Н. К вопросу о формировании глобальной правовой системы / Ю. Н. Оборотов // Наукові праці Національного університету «Одеська юридична академія». Т. 10 / голов. ред. С. В. Ківалов ; МОНмолодьспорт України, НУ "ОЮА". – Одеса : Юрид. л-ра, 2011. – C. 229-236.
Keywords: глобализация; глобальная культура; глобальный менталитет; транснациональное право; менталитет; глобальное право; глобальная правовая система; глобалізація; глобальна культура; глобальний менталітет; транснаціональне право; менталітет; глобальне право; глобальна правова система; globalization; global culture; a global mindset; transnational Law; mentality; global Law; a global legal system